AN ABATTOIR SURVEY OF PNEUMONIA LESIONS IN SLAUGHTER PIGS IN CEBU, PHILIPPINES - Destajo, Ruby H; Bolo, Rhia Jean A; Jabonero, Resalie A; Alcuirez, John Paul C (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
A cross-sectional study was conducted in four selected abattoirs from December 2018 to February 2019 to determine the prevalence of gross swine enzootic pneumonia - like lung lesions in slaughter pigs in Cebu, Philippines. A total of 954 pig lungs were evaluated using the Goodwin's lung score for enzootic pneumonia. Lesions indicative of pneumonia were found in 85.43% of the lungs examined. Higher prevalence was observed in fatteners (68.87%) and in commercial slaughter pigs (44.76%). Prevalence in the three sites were 84.56% (Site1), 97.49% (Site2), and 77.20% (Site3). Site 2 had the highest prevalence (55.23%) of severe gross lung lesions observed while Sites 2 and 1 had 47.23% and 21.08% respectively. Findings in this study showed a high prevalence of pneumonia in slaughter pigs as observed in other countries, confirming the status of enzootic pneumonia as a major respiratory problem endemic in swine herds worldwide.